Review Pendapatan Asli Daerah: Pendekatan Analisis Horisontal Dan Vertikal - Syamsul Syamsul; Lilia Fifiani (Universitas Gorontalo, 2019)
This study aims to evaluate the Local Original Revenue (PAD) using a horizontal and vertical analysis approach. This type of research is descriptive qualitative research. The data analyzed are the PAD data of the Parigi Moutong Government for the period 2013-2017. The results of the analysis show that the average growth of the PAD component is 61.19% and the majority of the contribution rate of each PAD component is <30%. This research contributes as an additional reference for policymakers in the future management of PAD in Parigi Moutong Government. Furthermore, this research can be used as an additional reference for further research related to the same topic as this research.